ANTIMUTAGENIC EFFECT OF CARROT (Daucus carota) ON INDUCTION OF STREPTOMYCIN AND RIFAMPICIN RESISTANT MUTANTS IN BACTERIAL SYSTEMS - Ilham A. Khalaf (Mesopotamia Journal of Agriculture)
G-system was used to study the cytotoxicity and genotoxicity of carrot root juice. The system composed of three bacterial strains: G3 (Bacillus spp), G12 (Arthrobacter spp), G27 (Brevibacterium spp). The strains are Gram positive, sensitive to crystal violet, Streptomycin (10µg / ml) and Rifampicin (20µg / ml) (Chromosomal markers). Effect of carrot root juice at different concentrations 50, 100, 200µl on log culture suspended cells was studied. Cyclophosphamide (Cp) drug (Mutagen) was used at 1, 10, 50, 100 µg/ml. The juice and the mutagen were tested for cytotoxicity by estimating the survival index (Sx), and genotoxicity by estimating the mutant frequency of Streptomycin and Rifampicin resistance. Results showed that low conc (s) (50, 100µl) of carrot juice had no cytotoxic or genotoxic effect, while 200µl had slight cytotoxic and genotoxic activity, therefore 100µl quantity was used for subsequent investigations. Cp had both cytotoxic and genotoxic activity. The effect of different combinations between carrot and Cp was studied (Using juice and mutagen together, treating cells with juice before and after mutagen treatment), the results revealed that carrot juice provided cells with high protection against cytotoxicity and genotoxicity, the protection effect ranged 80– 100 %.